Efficacy and tolerability of hyaluronic acid, tea tree oil and methyl-sulfonyl-methane in a new gel medical device for treatment of haemorrhoids in a double-blind, placebo-controlled clinical trial - Joksimovic, N; Spasovski, G; Joksimovic, V; Andreevski, V; Zuccari, C; Omini, C F (Springer Science and Business Media LLC, 2012)
Topical formulations are widely used in anti-haemorrhoidal treatment, but often lacking controlled clinical trials. Here, we report the results from a controlled clinical trial performed with a new gel medical device (Proctoial) containing hyaluronic acid with tea tree oil and methyl-sulfonyl-methane as major components. The total number of 36 haemorrhoidal patients (grade 1-3) was enrolled in a double-blind, placebo-controlled clinical trial and divided into 2 equal parallel groups. The anal pain, pain during defecation, visible bleeding, pruritus and irritation/inflammation were recorded before and after 14-day treatment using a visual analogue scale both by the investigators and by the patients. Safety and tolerability of the treatments were also recorded. The new gel medical device statistically significantly reduced all the symptoms after the treatment compared to placebo. The results indicated also a very good tolerability and safety of the treatments.